Avaliação dos efeitos de peptídeos isolados de veneno de serpentes no sistema cardiovascular de ratos - Alves, Pedro Henrique (2016)
The proline-riche-oligopeptides (PROs) were identified in the crude venom of snakes Bothrops jararaca (Bj), Bothrops cotiara (Bc) and Bothrops fonsecai (Bf). Previous studies have shown hypotensive/antihypertensive effects of the PROs in normotensive and hypertensive (SHR) rats. However, the direct effect of PROs in the aorta and heart isolated, as well as, the action mechanisms involved in these effects is unknown. In the presenty study, were evaluated the cardiovascular effect of six PROs, Bj-PRO-5a,-7a,-10c, Bc-PRO-10e, Bf-PRO-10d,-10f. The aortic rings, with (E+) or without (E-) endothelium, were preconstricted with phenylephine (Phe, 0.1 μmol/L), following increasing concentrations of PROs (0.1 nmol/L – 1 μmol/L) in presence or absence of a nonselective antagonist muscarinic receptors (Atropine, 3µmol/L), M1 muscarinic receptor antagonist (Pirenzepine, 1 µmol/L), synthase nitric oxide inhibitor (L-NAME, 1 µmol/L), adenylyl cyclase inhibitor (MDL 12.330A, 3 µmol/L), guanylyl cyclase inhibitor (ODQ, 3µmol/L) or argininosuccinate synthetase inhibitor (MDLA, 1 µmol/L). To evaluated the coronary and cardiac contractility effects of PROs, the hearts were perfused according Langendorff technique. The hearts were perfused for a basal period with Krebs Ringer solution containing the PROs (0.05 or 5 nmol/L) in presence or absence of L-NAME (10 nmol/L), ODQ (200 nmol/L) or MDL (1 µmol/L). The PROs utilized in this study induced endothelium-dependend vasorelaxation in aortic rings of Wistars and SHRs. Atropine and pirezenpine blocked the vasorelaxant effect of Bj-PRO-7a in isolated aorta from Wistar and SHR. L-NAME, ODQ or MDL inhibited the aortic vasorelaxation induced by Bj-PRO-7a and Bj-PRO-10c in both strains. MDLA inhibited the Bj-PRO-10c-induced vasorelaxation in aortic rings of SHR, but not in Wistar. Just the peptides Bj-PRO-7a and Bj-PRO-10c promoted a significant coronary vasodilatation in isolated heart from Wistar and SHR rats. The coronary vasodilatation induced by Bj-PRO-7a was inhibited in the presence of L-NAME in isolated heart from Wistar. Already in isolated heart from SHR this effect was abolished by L-NAME, ODQ or MDL. The Bc-PRO-10e and Bf-PRO-10f did not induce significant effects on cardiac contractility. However, the Bj-PRO-5a, -7a, -10c and Bf-PRO-10f promoted negative inotropic effect in the isolated hearts from Wistar and/or SHR. This effect in isolated hearts perfused by Bj-PRO-7a was inhibited in the presence of L-NAME in Wistars. Differently, the effect of Bj-PRO-10c was blocked by L-NAME, ODQ or MDL in both strains. Sumarizing, the PROs utilized in this study induced endothelium-dependend vasorelaxation. The data demonstrated participation of pathways NO/GCs/GMPc and AC/AMPc in the vasorelaxant effect of peptides Bj-PRO-7a and Bj-PRO-10c. In addition, the muscarinic receptors are involved in the vasorelaxant effects induced by peptide Bj-PRO-7a in aortic rings from Wistar and SHR rats. Moreover, the negative inotropic effect induced by Bj-PRO-7a and Bj-PRO-10c is linked with activation of NO in cardiomyocyte of normotensive and hypertensive rats.